PENGGUNAAN WHATSAPP, GOOGLE MEET, DAN ZOOM SEBAGAI MEDIA PEMBELAJARAN SELAMA PANDEMI COVID 19 - Roby Firmandil Diharjo (UNZAH Genggong, 2021)
The COVID-19 pandemic has had an impact on the learning situation at both the elementary and tertiary levels. The search for learning solutions continues to be carried out so that learning runs in a planned manner. The purpose of this conceptual research is to utilize technological developments as a tool or alternative to make learning activities successful. The whatsapp, google meet, and zoom applications are one of the technologies that are indicated to have solutions for learning activities during the covid pandemic. The application of this application is used as an evaluation material during the covid 19 pandemic learning.Keywords: whatsapp, google meet, zoom, learning media